The Philosophy of the Pengurip Gumi Ceremony at Pura Luhur Batukaru In the Contemporary Era - I Ketut Subagiasta (International Proceeding On Religion, Culture, Law, Education, And Hindu Studies, 2022)
An article related to Hindu rituals taking place in Bali Indonesia, carried out in the Batukaru Temple area in the Wongaya Gede Village Penebel area of ??Tabanan Bali Indonesia named or writing entitled "The Philosophy of Pengurip Gumi Ceremony at Pura Luhur Batukaru in the Contemporary Era". The implementation is carried out from November 2019 to April 2020. The main meaning of the ceremony is to ask God Almighty or Ida Sang Hyang Widhi Wasa to grant the safety and welfare of mankind in this universe.